Društva za Združene narode kot zagovorniki in kritično oko Organizacije združenih narodov - Aralica, Adriana (Teorija in praksa, 2016)
The article analyses the role of civil society in the United Nations (UN) system with United Nations Associations (UNAs) as a case study. UNAs - national civil society organisations with diverse programmes and memberships - represent a link between citizens of the world and the UN. The article presents UNA Slovenia's success stories and focuses on the pioneering role of UNA Slovenia in the field of global education in former Yugoslavia and opportunities to reinforce this role. UNAs will continue to be flag-bearers of UN issues and values. Establishing dialogue with relevant stakeholders, advocating UN values and goals and taking a critical look at UN activities with a special focus on youth as a target group presents an opportunity to strengthen UNA Slovenia as the central forum for discussions on global challenges.
Keywords: Advocacy; Civil society; Civilna družba; društva za ZN; globalno učenje; International organizations; Mednarodne organizacije; Organizacija združenih narodov; Slovenia; Slovenija; Zagovorništvo